(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Golodenko S. M. Astronomical observations as a way of forming astronomical knowledge. The article refers to the astronomical observations, which are a source of factual knowledge, which makes it possible explanations of astronomical phenomena, the study of the physical characteristics of celestial bodies and the physical explanations of the processes in space.